12 Hz electromagnetic field changes stress-related hormones of rat - Mahdavi, Seyed Mohammad; Rezaei-Tavirani, Mostafa; Nikzamir, Abdolrahim; Ardeshirylajimi, Abdolreza (Archives of Advances in Biosciences, 2014)
Due to the increasing presence of electromagnetic radiation in advanced societies, investigation of the effects of this radiation on humans has attracted the interest of many researchers. The non- ionizing radiation can induce numerous effects through biomolecules in the tissue and cells. In the current study, effects of 12 Hz electromagnetic waves investigated on neuronal hormone levels in rat animal model in 1, 3, 7, 14 and 21 days after exposure. The levels of Adrenocorticotropic hormone (ACTH), Adrenaline, melanocortin-2 receptor (MC2R), corticostrone, α1-receptor and D-Glucose were evaluated by ELISA methods. Exposure with 12 Hz electromagnetic waves did not alter in glucose and MC2R levels in rats compared with control groups. Plasma ACTH and adrenaline concentrations as two important stress-related hormones increased significantly 1 and 3 days after irradiation respectively. Also corticostrone and alpha a1-receptor decreased significantly at some days during the period of study in irradiated rats. Our data demonstrated that faced with 12 Hz electromagnetic wave could be considered as a stress inducer and also time of exposure have critical role in stress induce.